Use of DEMATEL and COPRAS method to select best alternative fuel for control of impact of greenhouse gas emissions. (August 2021) - Narayanamoorthy, Samayan; Ramya, L.; Kalaiselvan, Samayan; Kureethara, Joseph Varghese; Kang, Daekook
Abstract: Generation of energy is a vital process for sustenance of human life. Quality of human life is undoubtedly linked to the efficient generation and use of energy. The choice of alternative fuels is of the utmost significance due to the decline of fossil fuel reserves and their effect on global warming. One of the most important areas of research all over the world is the generation and distribution of sustainable energy. There are, in fact, many sustainable fuel resources. In this study, we describe the problem of selecting alternate fuel using novel types of hesitant multi criteria decision-making equation methods. The considered fuel systems are Electricity, natural gas, biodiesel, ethanol, and propane. In the selection of alternative fuels, quantity, quality of performance, cost, and efficiency among others, have to be taken into account. The alternatives selected should, for example, increase the speed of buses, and provide for greater mileage while and not affecting the environment. Here, the DEMATEL (Decision Making Trial and Evaluation Laboratory Model) method is used to determine the weights of the criteria and the COPRAS (Complex Proportional Assessment) method is used to calculate the ranking of the alternatives. The main objective of this research paper is to select the best alternative, based on environmental safety, C O 2 emission level, technical cost, and fuel cost. Thus a better alternative is selected with the selected alternatives and criteria. The results of this research are summarized as follows. These are natural gas ( R 2 ) > propane ( R 5 ) > biodiesel ( R 3 ) > electricity ( R 1 ) > ethanol ( R 4 ). The numeric values of these selected alternatives are R 2 = 1 > R 5 = 0.5215 > R 3 = 0.4904 > R 1 = 0.4887 > R 4 = 0.3299 . Graphical abstract: Image 1 Highlights: The MCDM approach of control to greenhouse emissions by choosing alternative fuels. The characteristic of each alternative fuels are described. We propose the DEMATEL and COPRAS method for Normal Wiggly hesitant set. Comparative and sensitivity analysis for alternative fuel selection is defined.